LOCATION AND GENDER ANALYSIS OF CLIMATE CHANGE VULNERABILITY AND IMPLICATION FOR POVERTY REDUCTION IN TARABA STATE, NIGERIA - BULUS, ANDEYANGTSO; MADUEME, STELLA IFEOMA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2022)
The study examined location and gender dimension of climate change and its implication for poverty reduction in Taraba State, Nigeria. The study used a multi-stage sampling technique, and interviewed 492 respondents from 12 communities in 6 local government areas. Adopting the Inter-Governmental Panel on Climate Change (2007) and Deressea, Hassan, and Ringer (2008) Vulnerability Index, the study found that Taraba North is the least vulnerable among the three senatorial zones followed by Taraba South while Taraba Central senatorial zone is the most vulnerable. Similarly, the result suggested that male farmers were more vulnerable than their female counterparts. On the basis of the results, the study recommended the need to improve the adaptive capacity of farmers in Taraba State through the strengthening of those variables that improve adaptive capacity such as training/seminar as well the government providing facilities for farmers to enable them engage in dry season farming.